The association of apolipoprotein E ε4 allele on cognitive function in middle age - Seppälä, Anna (My University, 2020)
Apolipoprotein E (APOE) is a lipid transport protein which in addition to its primary function has allele specific effects e.g. on cognition and cardiovascular health. There are three alleles of the APOE gene: ε2, ε3 and ε4. APOE ε4 allele is thus far the strongest known genetic risk factor for late-onset sporadic Alzheimer’s disease. Whereas it has been less researched how ε4 allele affects cognitive function in non-demented adolescents and adults. Although several studies have found that the deleterious effects of the ε4 allele on cognition starts to emerge in subjects aged >55–60 years, previous studies conducted on younger non-demented subjects have inconsistently connected ε4 allele both to beneficial and deleterious effects. The association of APOE ε4 allele on cognitive function in middle age is further investigated in this study. This study leverages the data from The Cardiovascular Risk in Young Finns Study (YFS). YFS is a large longitudinal population-based study which piloted in 1980 and aims to research how cardiovascular risk factors in childhood and youth affect the onset of diseases in adulthood. The latest follow-up study was conducted in 2011, when the subjects were 34 to 49 years old. Cognitive function was assessed using computer-based test battery (CANTAB®) which allowed extensive testing of different cognitive domains (e.g. visual memory, new learning, executive functions, working memory and psychomotor speed). The sample used in this study consisted of N=1909 subjects with data on APOE genotype and cognitive function. The results showed that in the oldest age group (49-year-olds) ε4 allele was associated with better visual memory and ability of new learning (performance in CANTAB® PAL-test) in males with low education level (education years <15 years). No associations between the ε4 allele and cognitive function was observed in other age groups.
Keywords: apolipoprotein E, ε4 allele, cognition, middle age